2018
DOI: 10.7150/thno.21524
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type IDH2 promotes the Warburg effect and tumor growth through HIF1α in lung cancer

Abstract: Hotspot mutations of isocitrate dehydrogenase 1 and 2 (IDH1/2) have been studied in several cancers. However, the function of wild-type IDH2 in lung cancer and the mechanism of its contribution to growth of cancer cells remain unknown. Here, we explored the role and mechanism of wild-type IDH2 in promoting growth of lung cancer.Methods: Information regarding genomic and clinical application focusing on IDH2 in cancer was examined in several databases of more than 1,000 tumor samples. IDH2 expression was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 47 publications
6
57
0
Order By: Relevance
“…Moreover, a close correlation was found between ERO1L expression and glycolytic components, including glucose transporter, glycolytic enzymes, and lactate transporter ( Figure S3 ). The Warburg effect can enable rapid cell proliferation by providing abundant cellular buildings for biosynthetic pathways, including nucleotides, lipids, and nonessential amino acids 29 - 31 . Therefore, we investigated whether the effect of ERO1L on PDAC is associated with its ability to modulate the Warburg effect.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a close correlation was found between ERO1L expression and glycolytic components, including glucose transporter, glycolytic enzymes, and lactate transporter ( Figure S3 ). The Warburg effect can enable rapid cell proliferation by providing abundant cellular buildings for biosynthetic pathways, including nucleotides, lipids, and nonessential amino acids 29 - 31 . Therefore, we investigated whether the effect of ERO1L on PDAC is associated with its ability to modulate the Warburg effect.…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemistry was performed on 2.5–3.0‐μm formalin‐fixed, paraffin‐embedded (FFPE) whole‐tissue sections, as described in previous studies 13–19 . Briefly, antigens were retrieved in a pressure cooker for 2.5 min.…”
Section: Methodsmentioning
confidence: 99%
“…129 Specially, studies also found that IDH1 is significantly downregulated in clear cell renal cell carcinoma (ccRCC) compared with normal kidney cells, suggesting that IDH1 may function as a candidate tumor suppressor for ccRCC. 130,131 Most studies indicate that IDH2 is also significantly upregulated in ESCC, 132 ovarian cancer, 133 lung cancer and other types of cancer, 134 playing a pro-oncogenic role. Overexpression of IDH2 decreases ROS levels and increases cancer cell growth.…”
Section: Pentose Phosphate Pathwaymentioning
confidence: 99%
“…Most studies indicate that IDH2 is also significantly upregulated in ESCC, 132 ovarian cancer, 133 lung cancer and other types of cancer, 134 playing a pro-oncogenic role. Overexpression of IDH2 decreases ROS levels and increases cancer cell growth.…”
Section: Molecular Mechanisms Of Nadph Homeostasis In Cancermentioning
confidence: 99%